Fast prenatal development of the NPY neuron system in the neocortex of the European wild boar, Sus scrofa - Ernst, Laura; Roos, Johannes; Engelhardt, Maren (Brain structure & function, 2018)
Knowledge on cortical development is based mainly on small rodents besides primates and carnivores, all being altricial nestlings. Ungulates are precocial and born with nearly mature sensory and motor systems. Almost no information is available on ungulate brain development. Here, we analyzed European wild boar cortex development, focusing on the neuropeptide Y immunoreactive (NPY-ir) neuron system in dorsoparietal cortex from E35 to P30. Transient NPY-ir neuron types including archaic cells of the cortical plate and axonal loop cells of the subplate which appear by E60 concurrent with the establishment of the ungulate brain basic sulcal pattern. From E70, NPY-ir axons have an axon initial segment which elongates and shifts closer towards the axon’s point of origin until P30. From E85 onwards (birth at E114), NPY-ir neurons in cortical layers form basket cell-like local and Martinotti cell-like ascending axonal projections. The mature NPY-ir pattern is recognizable at E110. Together, morphologies are conserved across species, but timing is not: in pig, the adult pattern largely forms prenatally.